ANALISIS PESAN DAKWAH TAYANGAN “UNTUK APA KITA HIDUP DI DUNIA” OLEH USTAD ABDUL SOMAD PADA KANAL YOUTUBE TAMAN SURGA. NET - Khamim, Nur; Fitri, Ahmad Asrof; Sobirin (Journal of Islamic Studies, 2023)
This research aims to 1) To explain the message of da'wah delivered by Ustadz Abdul Somad with the title ‘For What We Live in the World’ on Youtube Taman Heaven.Net. 2) To explain the positive impact of the community on the da'wah message delivered by Ustadz Abdul Somad with the title ‘For What We Live in the World’ on Youtube Taman Langit.Net. The research This research uses the library research method with the following data collection techniques: observation techniques, communication techniques, measurement techniques, and techniques for reviewing documents and books related to the message of preaching the show ‘For What Are We Living in the World’ By Ustad Abdul Somad. From this research, the results obtained are: 1) The message of da'wah delivered by Ustad Abdul Shomad in the Taman Heaven.Net Youtube account with the title ‘For What We Live in the World’ contains messages of da'wah, aqidah, morality, and sharia. 2) The positive impact of the community on the da'wah message delivered by Ustadz Abdul Somad with the title ‘For What We Live in the World’ on Youtube Taman Langit.Net, there were 2562 viewers who watched the Youtube channel and gave positive comments.